Fundamentals of 3D food printing and applications - Godoi, Fernanda C. (Elsevier Ltd. : Academic Press, 2018)
Fundamentals of 3D Food Printing and Applications provides an update on this emerging technology that can not only create complex edible shapes, but also enable the alteration of food texture and nutritional content required by specific diets. This book discusses 3D food printing technologies and their working mechanisms within a broad spectrum of application areas, including, but not limited to, the development of soft foods and confectionary designs. It provides a unique and contemporary guide to help correlate supply materials (edible inks) and the technologies (e.g., extrusion and laser based) used during the construction of computer-aided 3D shapes. Users will find a great reference that will help food engineers and research leaders in food science understand the characteristics of 3D food printing technologies and edible inks.